Functionalization effect on a Pt/carbon nanotube composite catalyst: a first-principles study. Issue 32 (1st August 2016) - Kim, Byung-Hyun; Lee, Kwang-Ryeol; Chung, Yong-Chae; Park, Mina
Abstract : Chemical interactions between Pt and both pristine and defective carbon nanotubes (CNTs) that were functionalized with various surface functional groups, including atomic oxygen (–O), atomic nitrogen (–N), hydroxyl (–OH) and amine (–NH2 ) groups, were investigated through first-principles calculations. Abstract : Chemical interactions between Pt and both pristine and defective carbon nanotubes (CNTs) that were functionalized with various surface functional groups, including atomic oxygen (–O), atomic nitrogen (–N), hydroxyl (–OH) and amine (–NH2 ) groups, were investigated through first-principles calculations. Our calculations suggest that the oxygen or nitrogen of the surface functional group can promote better structural stability of a Pt/CNT complex in terms of the binding energy enhancement between Pt and CNTs. Enhanced binding of the Pt/CNT complex would improve the long-term durability of the complex and thus enhance the catalytic activity of Pt catalysts supported on CNTs. Among the functional groups investigated, atomic nitrogen resulted in the most consistent increase in the Pt binding energies on pristine or defective CNTs. Moreover, atomic nitrogen decoration on the surface of CNTs rather than substitution into the CNTs appears to be more desirable. A d-band centre analysis and H2 adsorption calculations also revealed that the catalytic activity of Pt can be improved via efficient functionalization of the CNT support.